1989
DOI: 10.1346/ccmn.1989.0370109
|View full text |Cite
|
Sign up to set email alerts
|

Alcohothermal Treatments of Gibbsite: Mechanisms for the Formation of Boehmite

Abstract: Abstract--Gibbsite samples of various particle sizes (0.2-80 #m) were heated at 250~ in a series of straight-chain primary alcohols under the autogenous vapor pressure of the alcohol (alcohothermal treatment of gibbsite). The treatment in ethanol yielded pure boehmite, the morphology of which was similar to that of the boehmite obtained by hydrothermal treatment of gibbsite. In middle-range alcohols, the boehmite yields were low (50% if 80 t~m gibbsite was used), and the products were contaminated by a poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 35 publications
(33 reference statements)
1
14
0
2
Order By: Relevance
“…On the other hand, water molecules were not stabilized in aprotic solvents (hydrocarbons and related compounds) and the high fugacity (activity) of water facilitated the hydrothermal reaction of gibbsite resulting in complete formation of boehmite. Note that if gibbsire alone was heated in an autoclave at 250~ it transformed completely to boehmite (Inoue et aL, 1989). Apparently (ostensibly), the gibbsite structure was stabilized by the presence ofglycolic media; however, this stabilization effect was not due to the direct interaction between glycol molecules and gibbsite, but was due to lowering the fugacity (activity) of water by the glycol Figure 6.…”
Section: Xrd Profiles Of the Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, water molecules were not stabilized in aprotic solvents (hydrocarbons and related compounds) and the high fugacity (activity) of water facilitated the hydrothermal reaction of gibbsite resulting in complete formation of boehmite. Note that if gibbsire alone was heated in an autoclave at 250~ it transformed completely to boehmite (Inoue et aL, 1989). Apparently (ostensibly), the gibbsite structure was stabilized by the presence ofglycolic media; however, this stabilization effect was not due to the direct interaction between glycol molecules and gibbsite, but was due to lowering the fugacity (activity) of water by the glycol Figure 6.…”
Section: Xrd Profiles Of the Productsmentioning
confidence: 99%
“…In aprotic solvents gibbsite transformed completely into boehmite, whereas in protic solvents, unreacted gibbsite remained. Inoue et al (1989) examined the boehmite formation from gibbsite in alcoholic media and found that in an alcohol having a carbon number > 5 (higher alcohols), the boehmite yield increased with an increase in the carbon number of the alcohol. They attributed this increase in the boehmite yield to the increase in fugacity of water formed by partial dehydration ofgibbsite and concluded that in these higher alcohols, boehmite formed by means of an intraparticle hydrothermal reaction mechanism, originally proposed by de Boer et al (1954ade Boer et al ( , 1954bde Boer et al ( , 1964 for the formation of boehmite during the thermal dehydration of gibbsite.…”
Section: Xrd Profiles Of the Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many chemical routes, boehmite and bayerite have been used as the starting materials for the preparation of alumina. Boehmite is prepared by various methods such as hydrothermal treatment of gibbsite (Inoue et al 1989), hydrolysis of alkoxides (Yoldas 1975) or aluminium nitrate solutions (Mani et al 1991), etc. Aluminium metal has also been used as a precursor for the synthesis of aluminium hydroxides and these hydroxides are used to prepare alumina particles (Kannan et al 1997;Mo and Yuan 1993;Thiruchitrambalam et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, one of the present authors showed that α-alumina was synthesized from microcrystalline gibbsite (Al(OH) 3 ) in 1,4-butanediol at 285 °C [17], much lower temperature than that required by the hydrothermal reaction. He also examined the reaction of gibbsite in a series of alcohols and found that two different reactions took place depending on the carbon number of the alcohol [18]. When higher alcohols were used as the reaction media, hydrothermal reaction by the water formed by thermal dehydration of the starting material took place [16].…”
Section: Introductionmentioning
confidence: 99%